Hura crepitans Seed Oil: An Alternative Feedstock for Biodiesel Production. (10th August 2014) - Adewuyi, Adewale; Awolade, Paul O.; Oderinde, Rotimi Ayodele
Abstract : Oil was extracted from the seed of Hura crepitans using hexane in a soxhlet extractor and analyzed for iodine value, saponification value and free fatty acid content. The dominant fatty acid in the oil was C18:2 (52.8 ± 0.10 %) while the iodine value was120.10 ± 0.70 g iodine/100 g. Biodiesel was produced from the oil using a two-step reaction system involving a first step of pretreatment via esterification reaction and a second step via transesterification reaction. The pretreatment step showed that free fatty acid in Hura crepitans seed oil can be reduced in a one-step pretreatment of esterification using H2 SO4 as catalyst. The biodiesel produced from Hura crepitans seed oil had an acid value of0.21 ± 0.00 mg KOH/g, flash point of 152 ± 1.10°C, copper strip corrosion value of 1A, calorific value of39.10 ± 0.30 mJ/kg, cetane number of45.62 ± 0.30, and density of0.86 ± 0.02 g cm −3 . The process gave a biodiesel yield of98.70 ± 0.40 % with properties within the recommended values of EN 14214.